Working time as an investment? The effects of unpaid overtime on wages, promotions and layoffs - Silke Anger (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2005)
Whereas the number of paid overtime hours declined over the last decade, a different trend can be observed for unpaid overtime work in Germany. We look at the future consequences for overtime workers, and therefore investigate the investment character of working time. We examine whether unpaid extra hours induce a higher likelihood of promotion and pay rise, and whether they reduce the risk of losing the job. Using longitudinal micro data from the GSOEP for the years 1991 to 2002 we find significant positive effects of unpaid overtime work on future payoffs, but also a positive impact on the probability of job loss. Therefore, we find only partial evidence for the investment character of unpaid overtime.
Keywords: J2; J3; J4; 330; overtime; unpaid work; promotion; wage growth; layoff